2015
DOI: 10.1097/jim.0000000000000216
|View full text |Cite
|
Sign up to set email alerts
|

Prediction by Low Plasma HbA1c of Mortality, Cardiac and Noncardiac Disease Risk: Modulation by Diabetic Status and Sex

Abstract: Inverse association of HbA(1c) with adverse outcomes in men and nondiabetic people indicates the involvement of HbA(1c) levels in autoimmune activation. The weaker inverse association with prevalent diabetes and in women is consistent with the operation of more pronounced confounding autoimmune processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The observation in the study from Israel that patients with chronic renal disease and a history of stroke presented further independent predictors of all-cause mortality supports this interpretation, insofar as such outcomes - and incident subclinical hypothyroidism - have been predicted by low HbA 1c levels [8,9] which likely represent an underlying autoimmune process [8]. Other than plasma HbA 1c , a number of proteins or polypeptides have been epidemiologically documented to be involved in the proinflammatory state and autoimmune activation (for details, see the brief review by Onat et al [11]).…”
mentioning
confidence: 53%
See 3 more Smart Citations
“…The observation in the study from Israel that patients with chronic renal disease and a history of stroke presented further independent predictors of all-cause mortality supports this interpretation, insofar as such outcomes - and incident subclinical hypothyroidism - have been predicted by low HbA 1c levels [8,9] which likely represent an underlying autoimmune process [8]. Other than plasma HbA 1c , a number of proteins or polypeptides have been epidemiologically documented to be involved in the proinflammatory state and autoimmune activation (for details, see the brief review by Onat et al [11]).…”
mentioning
confidence: 53%
“…In some ethnicities, for instance in Middle Eastern populations, other than in the study on Israeli patients cited above, we [8] and others [9] have recently reported that low HbA 1c levels predict long-term mortality. In an adjusted logistic regression analysis, each 0.7% (=1 SD) decrement of baseline HbA 1c predicted the composite endpoint among nondiabetic Turks (OR 1.49%, 95% CI 1.07-2.04) but not in the diabetic sample, while overall mortality in the whole sample was increased (OR 1.51%, 95% CI 1.05-2.17) [8].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Though several studies demonstrated a linear relationship between HbA1 c and several outcomes throughout the range of values [12,13], numerous recent studies showed that low HbA1 c in nondiabetic [14,15] or diabetic individuals [16,17] is associated with increased mortality. Such association suggests the involvement of HbA1 c levels in autoimmune activation and may be confined to one gender (e.g.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%